Bridging the digital divide: A narrative inquiry of EFL teachers’ Tech-PD Experiences in rural schools - Nanik Sri Rahayu; Uzlifatul Masruroh Isnawati; Ali Abdullah Ahmad Albayyan; Arcenia Maria Martins (JEELS (Journal of English Education and Linguistics Studies), 2026)
Despite the growing emphasis on digital literacy in education, research on technology-based professional development (Tech-PD) for English as a Foreign Language (EFL) teachers in rural and under-resourced contexts remains limited. Existing studies have examined technology integration in urban or well-resourced schools, teachers’ ICT competencies, and general challenges in online teaching, but there is a paucity of research exploring how senior EFL teachers in rural schools develop and apply digital skills through structured professional development. This study addresses this gap by investigating the experiences of six senior EFL teachers from rural schools in Indonesia who participated in a Tech-PD program. Using a narrative inquiry approach, data were collected through semi-structured interviews and analyzed via thematic analysis. Findings of the study demonstrates that context-sensitive Tech-PD can empower rural teachers to overcome infrastructural constraints and improve instructional practices. These findings have practical implications for teacher education and policy, emphasizing the need for continuous, hands-on, and collaborative professional development programs.